Penderitaan Warga Sipil: Analisis Wacana Berbasis Korpus atas Laporan Al Jazeera - Siti Nur Amalia; Titik Sudartinah; Pratomo Widodo (Al-Lisan: Jurnal Bahasa, 2026)
Background: The Russia-Ukraine conflict has generated an extensive humanitarian crisis in which media representations play a crucial role in shaping global perceptions of civilian suffering. While previous studies have shown that Western media tend to foreground Ukrainian victimhood and marginalize Russian civilian experiences, the representational practices of non-Western news organizations such as Al Jazeera remain underexplored. Aims: This study aims to examine how Al Jazeera represents Ukrainian and Russian civilians in its coverage of the Russia-Ukraine war and to identify ideological positioning reflected through linguistic patterns in the reporting. Method: The study employs a corpus-assisted discourse analysis (CADS) approach. A corpus of 20 Al Jazeera news articles published between 2022 and 2025 was analyzed using keyword frequency and collocation analysis, combined with qualitative interpretation based on Fairclough’s three-dimensional model and the concepts of civilian victimhood and empathy framing. Results: The analysis reveals a marked asymmetry in representation. Ukrainian civilians are predominantly associated with harm-related lexis and collocational patterns that emphasize vulnerability, humanitarian response, and demographic specificity. In contrast, Russian civilians appear far less frequently and are mainly linked to administrative or material damage descriptors, resulting in reduced emotional salience and narrative visibility. Implications: These findings provide empirical evidence that Al Jazeera constructs a hierarchy of civilian suffering that aligns with broader geopolitical narratives. The study contributes to corpus-based media discourse analysis by demonstrating how linguistic patterns reveal ideological positioning in conflict reporting and by highlighting the need for more balanced journalistic portrayals to support critical media literacy.